Intangible Cultural Heritage Kangwei Paintings: Literature Review and Outlook - Chang, Yuheng; Sangiamvibool, Arkom (Journal of Ecohumanism, 2024)
In recent years, many countries around the world have been implementing their own protective practices for intangible cultural heritage under the impetus of the Intangible Cultural Heritage Convention. This study will conduct an in-depth investigation into the intangible cultural heritage of Kangwei paintings in Yuanping City, Shanxi Province, China, exploring the process of cultural identity formation and the role of commercialization in the context of intangible cultural heritage revitalization, an area that has not been deeply researched before.Using the systematic literature review method, a review was conducted on 102 relevant documents and journal articles sourced from China National Knowledge Infrastructure (CNKI). Conduct a literature review from the perspectives of overall research characteristics, highly cited literature, theoretical foundations, and research methods.The results of the literature analysis are systematically elaborated from the aspects of the connotation and extension of Kangwei paintings, the practical mechanisms for the revitalization of Kangwei paintings as intangible cultural heritage, and related suggestions. The study found that the practical mechanisms for the revitalization of Kangwei paintings as intangible cultural heritage include institutional support mechanisms, theoretical consolidation mechanisms, collaborative mechanisms, social education mechanisms, application innovation mechanisms, and efficiency evaluation mechanisms, with no related research proposed.Therefore, based on the framework for the revitalization of Yuanping Kangwei paintings, the prospects of cultural identity and commercialization concepts are proposed: solidifying the theoretical foundation for the revitalization of Kangwei paintings as intangible cultural heritage, scientifically defining the connotations and extensions of Kangwei paintings, refining the cultural identity mechanism for the revitalization of Kangwei paintings as intangible cultural heritage, and enriching the theoretical foundation for the study of the commercialization of Kangwei paintings.